Moving in the right direction: Exploring the benefits of aerobic exercise in patients with recently elevated HbA1c levels - Eldein Mahgoub Mostafa, Mohamed Serag; Said, Shereen Mohamed; El-Sayed, Mohamed Salah; Elnaggar, Moustafa Ibrahim Ahmed; Abdelhady Alakhras, Abdelhamid Mohamed; Saleh, Marwa Mohamed Sayed Mohamed; Metawee, Shaimaa Mohamed; Elbedewy, Mohamed Ahmed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Regular exercise is recognized as having health advantages for all individuals, including enhancements in glycemic control, insulin efficacy, cardiovascular fitness, systemic inflammation, diabetes-related health concerns, and mental well-being. This study aimed to explore aerobic exercise benefits on patients with recently elevated HbA1c levels. A parallel, randomized controlled trial was conducted. A total of 60 participants were assigned to one of the two groups: The aerobic exercise (AE) Group and the Control group. Assessment included HbA1c (glycosylated hemoglobin), post-prandial blood sugar (PPBS) as well as fasting blood sugar (FBS) at baseline (at 0 weeks before the training) and after the 12 weeks (post-training). The results showed that in 12 weeks, there was a statistically substantial difference in the two groups' mean values of HbA1c, PPBS, as well as FBS (p<0.001). Current research findings indicate that a 12-week protocol of aerobic exercise may serve as an essential therapeutic approach for achieving glycemic control in patients with recently elevated HbA1c levels.